2018
DOI: 10.1002/ppul.24115
|View full text |Cite
|
Sign up to set email alerts
|

Aerodigestive dysbiosis in children with chronic cough

Abstract: Distinct dysbiotic signatures can be identified in the lower airway microbiota of pediatric subjects with chronic cough that relates to the degree and type of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…41,42 Investigations of the aerodigestive microbial composition in children with chronic cough revealed that the lower airway microbiota was enriched with Prevotella in the bacterial bronchitis group. 43 Airway microbiome studies have also found a high relative abundance of oral microbes, suggesting that recurrent microaspirations might influence the lower airway microbiota. 36,43 Especially in EA/TEF patients with a high number of possible aspirations associated with esophageal dysmotility and gastroesophageal reflux, the oral microbiota could have a major impact on the composition of the airway microbiome.…”
Section: Airway Microbiomementioning
confidence: 99%
See 2 more Smart Citations
“…41,42 Investigations of the aerodigestive microbial composition in children with chronic cough revealed that the lower airway microbiota was enriched with Prevotella in the bacterial bronchitis group. 43 Airway microbiome studies have also found a high relative abundance of oral microbes, suggesting that recurrent microaspirations might influence the lower airway microbiota. 36,43 Especially in EA/TEF patients with a high number of possible aspirations associated with esophageal dysmotility and gastroesophageal reflux, the oral microbiota could have a major impact on the composition of the airway microbiome.…”
Section: Airway Microbiomementioning
confidence: 99%
“…43 Airway microbiome studies have also found a high relative abundance of oral microbes, suggesting that recurrent microaspirations might influence the lower airway microbiota. 36,43 Especially in EA/TEF patients with a high number of possible aspirations associated with esophageal dysmotility and gastroesophageal reflux, the oral microbiota could have a major impact on the composition of the airway microbiome. For instance, Veillonella, another oral commensal, was found significantly enriched in the lower airway microbiome of orally fed, neurologically impaired children who frequently suffer from aspiration of food, oral secretions, and common reflux of gastrointestinal contents into the airways.…”
Section: Airway Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…Work from our group and others has extensively characterised the fungal component of the bronchiectasis microbiome (the Mycobiome) and highlights a high frequency of fungal sensitisation associated with worsening disease severity, lung function and exacerbations [35]. In chronic cough, microbiome analysis has been applied to paediatric patients which has illustrated an increased abundance of commensal taxa in the lower airway and the potential association of specific microbiome signatures with particular patients including asthma, bacterial bronchitis or neurologically impaired orally fed subjects [36]. These observations highlight the potential for characterising cough endotypes based on microbiome analysis, however, the specific influence of the microbiome in bronchiectasis-associated cough remains to be defined.…”
Section: The Inter-relationship Between Cough and Bronchiectasismentioning
confidence: 99%
“…This includes antibiotic perturbations which can decrease the abundance of presumed beneficial commensal bacteria and increase the risk of respiratory infections following a course of antibiotics 7 . Research has shown that upper airway and gastric microbiota can be found in lower airway lavage samples in children with chronic cough and impaired swallow, supporting a degree of microaspiration which may or may not have been clinically suspected 8,9 . Duvallet et al 9 showed there was a greater overlap between oropharyngeal‐lung microbiota than gastric‐lung microbiota highlighting that the care of children with concern for aspiration may benefit from increased focus on oropharyngeal dysphagia instead of antireflux surgeries such as the Nissen fundoplication or medications targeting gastroesophageal reflux.…”
Section: Introductionmentioning
confidence: 99%